Karpaty w twórczości Bohdana Ihora Antonycza i Jerzego Harasymowicza - Ksenicz, Andrzej (Acta Polono-Ruthenica, 2008)
The paper is an attempt to compare the artistic vision of the Carpathian Mountains in the poetry of the two outstanding authors. It has been made with reliance on the analysis of several significant aspects that might be noticed in both cases. They encompass such questions as, for instance, remaining in a given place and creating beauty in its spiritual/material dimensions as well as the historical existing of this area together with its inhabitants. The comparative fathoming of numerous poems and other poetic forms indicates decisive similarities between the two authors’ ways of artistic expression whose essential and one of the most original components is an exceptional capability of metaphorising presented world.